Krisis Kebangkrutan Tupperware dalam Perspektif Komunikasi Korporat: Pendekatan Analisis Isi - Dwi Ananda Amalia (LPPM Stikosa - AWS, 2024)
This research analyzes the corporate communication approach taken by Tupperware during the crisis and finally declared bankruptcy in 2024. As a brand that has been in operation for 78 years, Tupperware faced challenges in maintaining its position in the global market. This study aims to analyze how Tupperware's corporate communication handled this crisis through the method of content analysis of the company's public messages. This research examines the communication strategies implemented by Tupperware in dealing with the corporate crisis, including press statements, social media, and media coverage, to understand the impact and effectiveness of their communication in maintaining reputation and relationships with stakeholders. The study used a qualitative approach through content analysis of textual data such as written documents, press releases or media coverage. The results showed that Tupperware attempted to implement transparent crisis communication and sales system adjustments with media developments, but faced difficulties in adapting and managing media coverage (media narratives) and maintaining stakeholder trust. The implications of this research highlight the importance of strategic and planned communication in managing a bankruptcy crisis.